Startups in Algeria - Towards the promotion of the economic development movement as an alternative to wealth creation without depending on economic rents - Horiya Souiki (Indonesian Journal of Social Science Research, 2023)
The Algerian legislator sought to establish a legal framework for emerging enterprises whose managers aim to create and market new technologies with the intention of promoting the economic development and encouraging investment and innovation in the field of information and communication technology. For this, he first started by embodying a committee specialized in granting the label of an emerging enterprise or Startup, with the introduction of provisions that simplify the requirements and conditions for establishing a simple Joint-Stock Company with the label of a Startup. For the first time ever, the legislator added a number of amendments to the Labor Law and the Basic Law of Public Function in order to give the employee the possibility to invest in the private sector and establish his own enterprise. In addition, regarding the university student, the legislator gave him a chance to prepare a new form of graduation dissertation project about the creation of startup. In this case, this student can therefore benefit from financial support and funding. This would certainly make the university student a creator of new job positions, which will surely help to reduce the unemployment rate. The present study aims to carry out an analytical interpretation of the different recent legal texts in order to frame them within the Algerian law.